2010
DOI: 10.1016/j.jacc.2010.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Potential Modulator of Beta-Adrenergic–Associated Leukocyte Mobilization in Heart Failure Patients

Abstract: Background Clinical outcomes are worse for heart failure (HF) patients presenting with symptoms of depression. Sympathetically modulated immune dysregulation associated with depression may be one mechanism leading to worse prognosis. Objectives We sought to determine whether depressive symptoms are related to alterations in sensitivity of peripheral blood mononuclear cells (PBMC) to β-adrenergic agonists in HF patients by measuring in vitro chemotaxis (CTX) to isoproterenol (ISO) at rest and following acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Treatment adherence, lifestyle factors, platelet reactivity, dysregulation of the autonomic nervous system, dysregulated hypothalamic-pituitary-adrenal axis activity, and altered immune/inflammation responses were suggested as possible biobehavioural links 30–35. Among these factors, altered immune/inflammation responses are considered a leading mechanism of worse cardiovascular outcomes associated with depression, and increased serum CRP concentration, an independent risk factor for CAD, was also demonstrated in subjects with depression 30 34 35. However, in our study, serum hsCRP concentration was comparable among study groups, and no interaction was identified between LV function and serum hsCRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment adherence, lifestyle factors, platelet reactivity, dysregulation of the autonomic nervous system, dysregulated hypothalamic-pituitary-adrenal axis activity, and altered immune/inflammation responses were suggested as possible biobehavioural links 30–35. Among these factors, altered immune/inflammation responses are considered a leading mechanism of worse cardiovascular outcomes associated with depression, and increased serum CRP concentration, an independent risk factor for CAD, was also demonstrated in subjects with depression 30 34 35. However, in our study, serum hsCRP concentration was comparable among study groups, and no interaction was identified between LV function and serum hsCRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Increased β-adrenergic sensitivity is postulated to be associated with cardiac remodeling and progression of heart failure. 72 Anxiety reduces compliance with medications, resulting in shorter event-free survival. 73 No published studies on the combination of anxiety, epinephrine, and heart failure are available.…”
Section: Activation Of the Hpa Axismentioning
confidence: 99%
“…Dysfunctional autonomic nervousactivity may underlie both progressions of inflammation as well as elevated resting heart rate [14]. Elevated sympathetic activity modifies the inflammatory processand thereby promotes endothelial dysfunction and subsequent at hero progression [15]. So, The European Society of Hypertension/European Society of Cardiology guidelines recently proposed the inclusion of elevated heart rate when evaluating the cardiovascular risk profile of an individual [16].…”
Section: Discussionmentioning
confidence: 99%